Chemiresistive Sensor Arrays for Gas/Volatile Organic Compounds Monitoring: A Review - Rath, Ronil J.; Farajikhah, Syamak; Oveissi, Farshad; Dehghani, Fariba; Naficy, Sina (Advanced engineering materials, 2023)
Gas detection and monitoring are essential due to their direct impact on human health, environment, and ecosystem. Chemiresistive sensors are one of the most used classes of sensors for monitoring and measurement of gases thanks to their ease of fabrication, customizability, mechanical flexibility, and fast response time. While chemiresistive sensors can offer good sensitivity and selectivity to a particular gas in a controlled environment with known interferences, they may not be able to differentiate between various gases having similar physiochemical properties under uncontrolled conditions. To address this shortcoming of chemiresistive gas sensors, sensor arrays have been the subject of recent studies. Gas sensor arrays are a group of individual gas sensors that are arranged to simultaneously detect and differentiate multiple cross‐reactive gases. In this regard, various sensor array technologies have been developed to differentiate a given set of gases using multivariate algorithms. This review provides an insight into the different algorithms that are used to extract the data from the sensor arrays, highlighting the fabrication techniques used for developing the sensor array prototypes, and different applications in which these arrays are used. This review provides an insight into the development and future perspectives of chemiresistive gas sensor arrays for different applications including environmental monitoring, food safety, and medical diagnosis. This review covers different algorithms for data extraction from the sensor arrays, highlighting the fabrication techniques used for developing prototypes, while demonstrating different real‐world applications.